Assessing realized genetic gains in biofortified cassava breeding for over a decade: Enhanced nutritional value and agronomic performance - Delgado, Luis Fernando; Moreta, Danilo E.; Morante, Nelson; Lenis, Jorge Ivan; Aparicio, Johan Steven; Londoño, Luis Fernando; Salazar, Sandra Milena; Tran, Thierry; Ospina, Maria Alejandra; Luna-Melendez, Jorge Luis; Alzate, Jhon Larry Moreno; Vargas, Hernan Camilo; et al. (Wiley, 2024)
Biofortified cassava ( Manihot esculenta ) plays a crucial role in enhancing the nutritional value of this essential staple, particularly in regions with limited dietary diversity and prevalent nutritional deficiencies. The cassava program at the International Center of Tropical Agriculture has dedicated over a decade to increase β‐carotene content in biofortified cassava, simultaneously focusing on improving yield, dry matter, and plant architecture. This paper presents realized genetic gains in biofortified cassava by analyzing the data from replicated multilocation breeding yield trials at the target population of environments spanning a 10‐year period (2013–2022). Following data curation, we observed significant positive genetic gains per year for β‐carotene content (7.03%), fresh yield (4.15%), dry matter content (0.55%), and height at the first branch (1.29%). A negative correlation between β‐carotene content and dry matter content was observed within 78% of trials. Moreover, our study uncovered a significant negative correlation between β‐carotene content and fresh root yield ( r = −0.22, p < 0.01) and an unfavorable positive correlation between β‐carotene content and the number of branches ( r = 0.23, p < 0.01). Such negative correlations between β‐carotene content and farm‐preferred traits presented substantial challenges for the development of biofortified cassava varieties. This research showed significant genetic gains and navigated the complexities of biofortified cassava development, providing breeding insights to enhance nutritional value while optimizing agronomic performance.